Combination CTLA-4 Blockade and 4-1BB Activation Enhances Tumor Rejection by Increasing T-Cell Infiltration, Proliferation, and Cytokine Production - Curran, Michael A. (Public Library of Science, 2011)
BACKGROUND: The co-inhibitory receptor Cytotoxic T-Lymphocyte Antigen 4 (CTLA-4) attenuates immune responses and prevent autoimmunity, however, tumors exploit this pathway to evade the host T-cell response. The T-cell co-stimulatory receptor 4-1BB is transiently upregulated on T-cells following activation and increases their proliferation and inflammatory cytokine production when engaged. Antibodies which block CTLA-4 or which activate 4-1BB can promote the rejection of some murine tumors, but fail to cure poorly immunogenic tumors like B16 melanoma as single agents. METHODOLOGY/PRINCIPAL FINDINGS: We find that combining αCTLA-4 and α4-1BB antibodies in the context of a Flt3-ligand, but not a GM-CSF, based B16 melanoma vaccine promoted synergistic levels of tumor rejection. 4-1BB activation elicited strong infiltration of CD8+ T-cells into the tumor and drove the proliferation of these cells, while CTLA-4 blockade did the same for CD4+ effector T-cells. Anti-4-1BB also depressed regulatory T-cell infiltration of tumors. 4-1BB activation strongly stimulated inflammatory cytokine production in the vaccine and tumor draining lymph nodes and in the tumor itself. The addition of CTLA-4 blockade further increased IFN-γ production from CD4+ effector T-cells in the vaccine draining node and the tumor. Anti 4-1BB treatment, with or without CTLA-4 blockade, induced approximately 75% of CD8+ and 45% of CD4+ effector T-cells in the tumor to express the killer cell lectin-like receptor G1 (KLRG1). Tumors treated with combination antibody therapy showed 1.7-fold greater infiltration by these KLRG1+CD4+ effector T-cells than did those treated with α4-1BB alone. CONCLUSIONS/SIGNIFICANCE: This study shows that combining T-cell co-inhibitory blockade with αCTLA-4 and active co-stimulation with α4-1BB promotes rejection of B16 melanoma in the context of a suitable vaccine. In addition, we identify KLRG1 as a useful marker for monitoring the anti-tumor immune response elicited by this therapy. These findings should aid in the design of future trials for the immunotherapy of melanoma.